Masyarakat Majemuk dan Perawatannya - Parsudi Suparlan (Antropologi Indonesia, 2000)
Indonesia is a multicultural society consisting of more than 500 ethnic groups, cultures, and various religious beliefs. They are united as a nation by the national state system of Indonesia. The Indonesian state was built by the founding fathers on the basis of the ideology of 'Unity in Diversity' (Bhinneka Tunggal Ika). During the Soeharto regime, it was turned into a state based on militarism, violence, totalitarianism, and was centered in the hands of the powerful elites. In line with the violence, militarism and totalitarianism, there has been an active use of primordialism (ethnicity and Islamic religion as the political tools). In this article the author presents the essence of Indonesia's multiculturalism and its potentials to unite and break up as a nation, as well as solutions on how to take care and maintain a democratic multiculturalism.